Polyglutamine-Specific Gold Nanoparticle Complex Alleviates Mutant Huntingtin-Induced Toxicity. - Wahyuningtyas, D.; Chen, W.H.; He, R.Y.; Huang, Y.A.; Tsao, C.K.; He, Y.J.; Yu, C.Y.; Lu, P.C.; Chen, Y.C.; Wang, S.H.; Ng, K.C.; Po-Wen Chen, B.; et al. (ACS applied materials & interfaces, 2021)
Huntington's disease (HD) belongs to protein misfolding disorders associated with polyglutamine (polyQ)-rich mutant huntingtin (mHtt) protein inclusions. Currently, it is indicated that the aggregation of polyQ-rich mHtt participates in neuronal toxicity and dysfunction. Here, we designed and synthesized a polyglutamine-specific gold nanoparticle (AuNP) complex, which specifically targeted mHtt and alleviated its toxicity. The polyglutamine-specific AuNPs were prepared by decorating the surface of AuNPs with an amphiphilic peptide (JLD1) consisting of both polyglutamine-binding sequences and negatively charged sequences. By applying the polyQ aggregation model system, we demonstrated that AuNPs-JLD1 dissociated the fibrillary aggregates from the polyQ peptide and reduced its ?-sheet content in a concentration-dependent manner. By further integrating polyethyleneimine (PEI) onto AuNPs-JLD1, we generated a complex (AuNPs-JLD1-PEI). We showed that this complex could penetrate cells, bind to cytosolic mHtt proteins, dissociate mHtt inclusions, reduce mHtt oligomers, and ameliorate mHtt-induced toxicity. AuNPs-JLD1-PEI was also able to be transported to the brain and improved the functional deterioration in the HD Drosophila larva model. Our results revealed the feasibility of combining AuNPs, JLD1s, and cell-penetrating polymers against mHtt protein aggregation and oligomerization, which hinted on the early therapeutic strategies against HD.